1996
DOI: 10.1093/oxfordjournals.jbchem.a021523
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of a Novel Isoform of the Human UDP-Galactose Transporter, and of Related Complementary DNAs Belonging to the Nucleotide-Sugar Transporter Gene Family

Abstract: We described recently the molecular cloning of human UDP-galactose transporter 1 (hUGT1) [Miura, N. et al. (1996) J. Biochem. 120, 236-241]. Now we have characterized its isoform, hUGT2, that is most likely generated through the alternative splicing of a transcript derived from the UGT genomic gene, that also codes for hUGT1. Introduction of the open reading frame sequence of hUGT2 into a mouse cell line, Had-1, that lacks the UDP-galactose transporter, complemented the genetic defect of the mutant, as judged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
65
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 11 publications
2
65
0
Order By: Relevance
“…UGTrel1 is a gene of unknown function that has similarity with human UDP-galactose transporter genes (15). In humans, Muraoka et al (24) identified a gene related to UGTrel1 and reported that the product transports both UDPglucuronic acid and UDP-N-acetylgalactosamine.…”
Section: Fig 2 Subcellular Localization Of Papst1 Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…UGTrel1 is a gene of unknown function that has similarity with human UDP-galactose transporter genes (15). In humans, Muraoka et al (24) identified a gene related to UGTrel1 and reported that the product transports both UDPglucuronic acid and UDP-N-acetylgalactosamine.…”
Section: Fig 2 Subcellular Localization Of Papst1 Proteinmentioning
confidence: 99%
“…NST gene homologous to human UGTrel1 (UDP-galactose transporter-related isozyme 1) (15). Unexpectedly, the heterologous expression of PAPST1 in yeast Saccharomyces cerevisiae did not result in any nucleotide-sugar transport activity but revealed PAPS transport activity.…”
mentioning
confidence: 96%
“…cerevisiae HUT1 (scHUT1) encodes a putative hydrophobic protein with approximately 30% identity to human UDP-galactose transporter-related gene (UGTrel1) product, which is somewhat similar to human UDP-galactose transporter gene (UGT1) product, but the function is unknown (Ishida et al, 1996). We have found that the overexpression of scHUT1 in S. cerevisiae cells expressing S. pombe galactosyltransferase (Gma12p), stimulates in vivo galactosylation and in vitro UDP-galactose transport activity (Kainuma et al, this Issue).…”
Section: Introductionmentioning
confidence: 99%
“…Using PCR-based approaches, the murine UGT (11), a second isoform of the human UGT (12), and a full-length S. pombe UGT cDNA (13) were isolated. Sequence alignments reveal strong conservation of UGTs, since species as distant as human and S. pombe are 40% identical (see Fig.…”
mentioning
confidence: 99%